Neuromodulatory Effect of Thymoquinone in Attenuating Glutamate-Mediated Neurotoxicity Targeting the Amyloidogenic and Apoptotic Pathways - Fouad, Ibram Amin; Sharaf, Nadia Mohamed; Abdelghany, Ragwa Mansour; El Sayed, Nesrine Salah El Dine (Frontiers in Neurology, 2018)
Overexposure of the glutamatergic N-methyl-d-aspartate (NMDA) receptor to the excitatory neurotransmitter l-glutamic acid leads to neuronal cell death by excitotoxicity as a result of increased intracellular Ca2+, mitochondrial dysfunction, and apoptosis. Moreover, it was previously reported that prolonged activation of the NMDA receptor increased beta-amyloid (Aβ) levels in the brain. Thymoquinone (TQ), the active constituent of Nigella sativa seeds, has been shown to have potent antioxidant and antiapoptotic effects. The aim of the present study was to explore the neuromodulatory effects of different doses of TQ (2.5 and 10 mg/kg) against apoptotic cell death and Aβ formation resulting from glutamate administration in rats using vitamin E as a positive control. Behavioral changes were assessed using Y-maze and Morris water maze tests for evaluating spatial memory and cognitive functions. Caspase-3, Lactate dehydrogenase, Aβ-42, and cytochrome c gene expression were determined. TQ-treated groups showed significant decreases in the levels of all tested biochemical and behavioral parameters compared with the glutamate-treated group. These findings demonstrated that TQ has a promising neuroprotective activity against glutamate-induced neurotoxicity and this effect is mediated through its anti-amyloidogenic, antioxidant, and antiapoptotic activities.